The role and profile of the informal carer in meeting the needs of people with advancing Parkinson's disease. (4th March 2019) - Hand, Annette; Oates, Lloyd Louis; Gray, William Keith; Walker, Richard W.
ABSTRACT: Background: Many people with Parkinson's disease (PD) (PwP) require care from either informal or formal carers, due to worsening symptoms. Carer strain is a recognised consequence of caring. However there are few data on the role and profile of informal carers and if this impacts on carer strain. Method: People with moderate to advanced PD, with an informal carer were invited to participate. Data regarding motor and non-motor symptoms of the participant, along with demographics, tasks and duration of caring and health issues of the carer were collected. Results: One-hundred and fifteen participants and their carer were recruited. Mean carer age was 70.7 years, 66.1% were female caring for a median of 16 hours per day. Over 80% provided help in housework and companionship activities, 63.2% with dressing and 49.1% with feeding. There was a significant relationship between disease stage and level of strain. Participant age, physical and cognitive disability were significantly associated with greater care need. High care need was associated with poor carer quality of life. Conclusions: The care needs of PwP are considerable. To reduce carer strain and improve quality of life, carers' needs must be considered to enable them to carry on with their vital role.